Structural features of the Mozambique economy through the lens of a 2019 social accounting matrix - Sam Jones; Enilde Sarmento; Dirk Van Seventer; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This study presents and discusses structural features of the Mozambique economy through the lens of a recently constructed 2019 social accounting matrix (SAM). This is an important reality check of the SAM construction process since it brings together various data sources that are not necessarily consistent with each other into a single framework. A number of dimensions are explored including industry composition and factor earnings, imports and exports, household income and expenditure and some labour market data. Agriculture remains a dominant industry in Mozambique accounting for over 70 per cent of employment although its contribution to GDP is about 25 per cent. On the other hand, services, public and private together, represent 48 per cent of GDP and 21 per cent of employment. Manufacturing plays a minor role at 10 per cent of GDP and just over 4 per cent of employment, while mining with just over 11 per cent of GDP, accounts for just over 1 per cent of employment. In spite of the importance of agriculture for employment, a little over a third of household income is earned in rural areas. Some simple multiplier calculations show low economic integration.
Keywords: D31; D33; D57; E16; J21; 330; social accounting matrix; national accounts; supply-use table; balance of payments; labour force survey; income distribution